Effects of irrigation during the dry season on agronomic characteristics of cultivars of elephant grass - Botrel, Milton de Andrade; Alvim, Maurílio José; Xavier, Deise Ferreira (Pesquisa Agropecuaria Brasileira, 1991)
The study was carried out at the CNPGL/EMBRAPA, in the "Zona da Mata" region of Minas Gerais, Brazil, with the purpose of evaluating the effects of irrigation during the dry season on forage production, grass protein content, OM digestibility and aerial and basal tillering of the following cultivars of elephant grass (Pennisetum purpureum, Schum): Taiwan A-146, Mineiro, Cameroon, Elefante Pinda, Cana Africana, Mott and Kizozi. The experiment was arranged in a split-plot complete block design with two replications. Irrigation and lack of irrigation were the treatments studied in the plots, whereas the elephant grass cultivars were the ones examined in the sub-plots. Sprinkler irrigation which consisted of a 25 to 30 mm water sheet was applied from a uniform crosscut (19.06.88) to the beginning of the rainy season. Irrigation enhanced forage yield of all cultivars of elephant grass, but the seasonally of such a yield was hardly altered. In general, irrigation promoted increases in basal tillering bud did not influence the aerial one. There were no effects on forage quality.